PASSAPU SA’DAN-TORAJA - Karta Jayadi; Dian Cahyadi (Seminar Nasional LP2M UNM, 2019)
This study aims to identify artifacts of cultural products in the community within the ethnic scope of Bugis-Makassar-Toraja related to the origin, variety of forms, characteristics (identification tools) formed from the results of intangible cultural products. Especially in Sa'dan-Toraja ethnicity. The identification of cultural products is intended to make the perimeter boundaries of culture as a characteristic. This method of constructing identity is intended as a form of accountability for the indigenous community towards the formation of the character characteristics and attitudes of members of the cultural community towards the surrounding cultural community. Sociologically it is a form of cultural exclusions for cultural communities in the Bugis-Makassar-Toraja ethnic entity. Where these characters are manifestations of the conception of philosophical values and cultural philosophies of Bugis-Makassar-Toraja ethnicity summarized in